Author Correction: Calcium ion-induced formation of β-sheet/-turn structure leading to alteration of osteogenic activity of bone morphogenetic protein-2 - Wenjing Zhang (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.